1996
DOI: 10.1088/0953-4075/29/6/012
|View full text |Cite
|
Sign up to set email alerts
|

On the violation of the exponential decay law in atomic physics:ab initiocalculation of the time-dependence of the non-stationary state

Abstract: The detailed time dependence of the decay of a three-electron autoionizing state close to threshold has been obtained ab initio by solving the time-dependent Schrödinger equation (TDSE). The theory allows the definition and computation of energy-dependent matrix elements in terms of the appropriate N-electron wavefunctions, representing the localized initial state, 0 , the stationary scattering states of the continuous spectrum, U(ε), and the localized excited states, n , of the effective Hamiltonian QH Q, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 50 publications
5
45
0
Order By: Relevance
“…For the radioactive isotope 60 Co, Norman et al observed the decay out to 30 exponential lifetimes, whereas theoretically the deviation from exponential decay is expected at signal intensities of order 10 ÿ60 of the initial intensity corresponding to 140 lifetimes [5]. More recently, theoretical effort has been directed to a range of atomic states including spontaneous photon emission [6], or autoand photoionizing states with very small release energies (E 0:01 eV) [7]. A common feature for all these atomic systems are the well-defined energy levels, exhibiting only homogeneous broadening, accompanied by (nearly) Lorentzian line shapes and exponential lifetimes that are inversely proportional to the width of the energetic state distribution, @=ÿ.…”
mentioning
confidence: 99%
“…For the radioactive isotope 60 Co, Norman et al observed the decay out to 30 exponential lifetimes, whereas theoretically the deviation from exponential decay is expected at signal intensities of order 10 ÿ60 of the initial intensity corresponding to 140 lifetimes [5]. More recently, theoretical effort has been directed to a range of atomic states including spontaneous photon emission [6], or autoand photoionizing states with very small release energies (E 0:01 eV) [7]. A common feature for all these atomic systems are the well-defined energy levels, exhibiting only homogeneous broadening, accompanied by (nearly) Lorentzian line shapes and exponential lifetimes that are inversely proportional to the width of the energetic state distribution, @=ÿ.…”
mentioning
confidence: 99%
“…Indeed, about 15 years ago [3,4], we demonstrated the possibility of computing from first principles the time-resolved decay of prototypical unstable states of polyelectronic atoms. The computations produced energies, lifetimes, and energy distributions.…”
Section: Theory and Computation Of Time-resolved Quantities Concermentioning
confidence: 99%
“…The computations produced energies, lifetimes, and energy distributions. Most importantly, in view of the well-documented "law" of exponential decay (ED), emphasis was placed on the fundamental issue of determining the magnitudes of the deviation from ED for very long [3,4] and for very short [5] times, using as test cases not simple models and formal manipulations, but real many-electron systems where the operators causing the decay are nonrelativistic or relativistic (Breit-Pauli Hamiltonian) and where the N-electron wave functions include the information of electronic structure and of electron correlation.…”
Section: Theory and Computation Of Time-resolved Quantities Concermentioning
confidence: 99%
“…The following discussions revealed a number of possible mechanisms for non-exponential decay for long as well as short times (see, e.g., ). Different physical situations have been considered starting from a basic model of penetration through a delta-edged potential [5], and including such processes as the spontaneous decay in two-level systems [6], tunneling alpha-decay of atomic nuclei and cold electron emission from metals [7], single photon ionization of atoms [8], non-exponential decays in autoionizing states [9][10], decay of excited helium state [11], etc. Among these mechanisms one should mention frequent measurements which slow the evolution of a quantum system, hindering transitions to states different from the initial one.…”
Section: Introductionmentioning
confidence: 99%